2017
DOI: 10.1002/bmc.3915
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolite identification of acotiamide in rats using ultra‐performance liquid chromatography–quadrupole/time‐of‐flight mass spectrometry

Abstract: Acotiamide hydrochloride (ACT) is a drug used for the treatment of functional dyspepsia. Understanding which metabolites are likely to be formed in vivo is essential for interpreting pharmacology, pharmacokinetic and toxicology data. The metabolism of ACT has been investigated using a specific and sensitive liquid chromatography positive ion electrospray ionization high-resolution tandem mass spectrometry method. In vivo samples including rat plasma, urine and feces were collected separately after dosing healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Stress testing helps in identification of degradation products and degradation behaviour of drug [5,6]. The literature reveals there were few analytical methods available for determination of acotiamide by HPLC [7], LC-MS-MS [8], UPLC-Q-TOF-MS [9,10], stability indicating the method by UPLC-Q-TOF-MS (gradient mode) [11], this reported method based on UPLC method.…”
Section: Fig 1: Structure Of Acotiamidementioning
confidence: 99%
“…Stress testing helps in identification of degradation products and degradation behaviour of drug [5,6]. The literature reveals there were few analytical methods available for determination of acotiamide by HPLC [7], LC-MS-MS [8], UPLC-Q-TOF-MS [9,10], stability indicating the method by UPLC-Q-TOF-MS (gradient mode) [11], this reported method based on UPLC method.…”
Section: Fig 1: Structure Of Acotiamidementioning
confidence: 99%
“…As the drug was only approved recently, no reports were found in the literature on SIAM for ACM. Recently, we reported pharmacokinetic studies and characterization of metabolites of ACT in rat biological samples . In the present study, we have developed a SIAM for ACM and identified the degradation products of ACM by using ultra‐high‐performance liquid chromatography/electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry (UHPLC/ESI‐QTOF‐MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of impurities can have a significant impact on the product quality, safety and efficacy, hence the percentage level of impurities need to control in the drug substance as well as a drug product 5,6 . The literature review reveals that there were few analytical methods available for determination of acotiamide by HPLC 7 , LC-MS-MS 8 , UPLC-Q-TOF-MS 9,10 , identification of degradation products of acotiamide by UPLC/ESI-quadrupole TOF-tandem MS 11 .…”
mentioning
confidence: 99%